A COMPARATIVE STUDY ON THE USE OF DIGITIZATION IN UNIVERSITY AND SPECIAL LIBRARIES OF SRI LANKA - Pushpakumara, K.T.S. (degree of Master of Library and Information Science, 2007)
Digitization is the present hot topic in the library and information profession in Sri Lanka. However, almost all the librarians of Sri Lanka talks about automation of the library activities until last few years. Lot of guidelines and procedures for the library collections have developed in the field of digitization over a period of last few years in the world. However, for variety of reasons, digitization of library materials in Sri Lanka is fraught with many difficulties. Several workshops, training programs have already been launched to introduce digitization for libraries in Sri Lanka at present time. However, building a good library digital collection is a challenging task for libraries. This study describes some digitization initiatives in university library and special library sectors in Sri Lanka. This study attempts to understand and compare the present situation in digitization of library resources. The main aim of this study was to find out the current and planned digitization practices; obstacles and potentials, policies in use, digitization objectives, materials being digitized, nature of the digital content, funding sources and collaborative activities and to introduce suggestions which can be used to improve the current situation of digitization in university libraries and special libraries in Sri Lanka. Structured questionnaire was used as the main instrument for gathering of data from the sample. A total of 73 libraries were selected in this study. 35 university libraries and 38 special libraries were selected and questionnaires were sent to librarians of each selected library in order to gather data from them. However, 54 survey responses were received. 28 special libraries out of 38 had responded to the questionnaires while the university libraries respondent rate was 26 out of 35. The overall response rate to the survey was 74%.